PENGARUH LIKUIDITAS DAN DEBT TO ASSETS RATIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI - Firman, Dody; Batubara, Hade Chandra; Karimah , Devi (Catholic University Musi Charitas, 2020)
Assets Ratio to Return On Assets in automotive companies listed on the IDX for the period 2013 - 2017. The independent variables in this research are Current Ratio (CR) and Debt To Assets Ratio (DAR) and the dependent variable is Return On Assets (ROA). The object of this study is an automotive company listed on the IDX. The approach in this study uses an associative approach. The data collection technique used is secondary data obtained or collected in the form of documentation data published by the IDX, namely the company's financial statements, namely the company's ROA from the 2013 - 2017 period which tends to decline. The data analysis technique used is the classical assumption test, t-test, F test, and the coefficient of determination. Based on the F statistical test, it was found that the variables Current Ratio and Debt to Assets Ratio had no significant effect on Return On Assets in automotive companies listed on the IDX.